(untitled) (Revista Contexto & Saúde, 2023)
This is a scope review developed with the objective of mapping and synthesizing the strategies developed in the health care of the trans population. The research was carried out following the recommendations of the Prisma Extension for Scoping Reviews and included articles that discussed approaches, strategies, devices and tools developed in the health care of the transgender public, considering the confrontation with difficulties and particularities from the perspective of professionals and the problem of the professional-patient relationship in the context of care for this public. Data collection was carried out in six databases in June 2021 covering articles, dissertations and theses. The final sample consisted of fifteen articles published between 2008 and 2021. The published strategies were diverse in terms of their methodology and development context, and were presented in two categories: educational/training strategies and institutional/organizational strategies. It was concluded that existing strategies consist mainly of educational approaches aimed at raising the awareness of health professionals in relation to the specific needs and disparities that involve trans people, and these practices are considered effective and necessary.